Sustainable Design of a Nearly Zero Energy Building Facilitated by a Smart Microgrid - Habash, Gandhi; Chapotchkine, Daniel; Fisher, Peter; Rancourt, Alec; Habash, Riadh; Norris, Will (Journal of Renewable Energy, 2014)
One of the emerging milestones in building construction is the development of nearly zero energy buildings (NZEBs). This complex concept is defined as buildings that on a yearly average consume as much energy as they generate using renewable energy sources. Realization of NZEBs requires a wide range of technologies, systems, and solutions with varying degrees of complexity and sophistication, depending upon the location and surrounding environmental conditions. This paper will address the role of the above technologies and solutions and discusses the challenges being faced. The objective is to maximize energy efficiency, optimize occupant comfort, and reduce dependency on both the grid and the municipal potable water supply by implementing sustainable strategies in designing a research and sports facility. Creative solutions by the architectural and engineering team capitalize on the design of a unique glazing system; energy efficient technologies; water use reduction techniques; and a combined cooling, heating, and power (CCHP) microgrid (MG) with integrated control aspects and renewable energy sources.